Use of wound infusion catheters for delivery of local anesthetic following standing partial ostectomy of thoracolumbar vertebral spinous processes in horses is not associated with increased surgical site infections - Wickstead, Francesca A.; Milner, Peter I.; Bardell, David A. (Frontiers in Veterinary Science, 2024)
Background Wound infusion catheters (WICs) have been used in humans and some veterinary species for post-operative local anesthetic administration following a variety of surgical procedures, aiming to reduce post-operative analgesia requirements and improve patient comfort. Benefit in reduction in pain, post-operative analgesia requirements and length of hospital stay are well documented in humans, but use of WICs may not have been widely adopted in veterinary species due to the concern of increased complications, such as dehiscence or surgical site infection (SSI), creating a barrier to their use. This study aimed to evaluate the use of WICs in horses undergoing standing partial ostectomy surgeries, document complications and investigate if the incidence of SSI was equivalent between those horses that did and did not have a WIC. Methods Clinical records were searched between January 2010–December 2023 for horses undergoing standing partial ostectomy surgery of thoracolumbar vertebral spinous processes at one institution. Population variables (age, breed, bodyweight), placement of a WIC or not, post-operative complications, analgesia protocols and surgical time were recorded. Horses received up to 0.1 mg kg−1 bupivacaine (0.5 mg mL−1) every 6–8 h via the WIC where one was placed. To compare SSI complication incidence between using or not using a WIC, a proportional independent equivalence test was used. Results There were 64 horses included in the final analysis with a WIC placed in 29/64 horses (45.3%) and 35/64 (54.7%) having no WIC placed at surgery. Incidence of short-term SSI was 11.4% (no WIC used) and 13.8% (WIC used), respectively. The difference in proportion of SSI between the presence or absence of a WIC was not significant [−0.024 (90% CI −0.181; 0.133); p = 0.94]. Conclusion The incidence of SSIs was equivalent between groups whether a WIC was used or not. WICs should be considered as part of a multi-modal analgesic approach in the post-operative period. Further research into local anesthetic dosing and its impact on rescue analgesia requirements and pain-scores is warranted.